Prevalence of chronic chikungunya and associated risks factors in the French West Indies (La Martinique): A prospective cohort study. - Antoine Bertolotti; Marême Thioune; Sylvie Abel; Gilda Belrose; Isabelle Calmont; Raymond Césaire; Minerva Cervantes; Laurence Fagour; Émilie Javelle; Catherine Lebris; Fatiha Najioullah; Sandrine Pierre-François; et al. (Public Library of Science (PLoS), 2020)
BACKGROUND:The chikungunya virus (CHIKV) is a re-emerging alphavirus that can cause chronic and potentially incapacitating rheumatic musculoskeletal disorders known as chronic chikungunya arthritis (CCA). We conducted a prospective cohort study of CHIKV-infected subjects during the 2013 chikungunya outbreak in Martinique. The aim of this study was to assess the prevalence of CCA at 12 months and to search for acute phase factors significantly associated with chronicity. METHODOLOGY/PRINCIPAL FINDINGS:A total of 193 patients who tested positive for CHIKV RNA via qRT-PCR underwent clinical investigations in the acute phase (<21 days), and then 3, 6, and 12 months after inclusion. The Asian lineage was identified as the circulating genotype. A total of 167 participants were classified as either with or without CCA, and were analyzed using logistic regression models. The overall prevalence of CCA at 12 months was 52.1% (95%CI: 44.5-59.7). In univariate analysis, age (RD 9.62, 95% CI, 4.87;14.38, p<0.0001), female sex (RD 15.5, 95% CI, 1.03;30.0, p = 0.04), headache (RD 15.42, 95% CI, 0.65;30.18 p = 0.04), vertigo (RD 15.33, 95% CI, 1.47;29.19, p = 0.03), vomiting (RD 12.89, 95% CI, 1.54;24.24, p = 0.03), dyspnea (RD 13.53, 95% CI, 0.73;26.33, p = 0.04), intravenous rehydration (RD -16.12, 95% CI, -31.58; -0.66 p = 0.04) and urea (RD 0.66, 95% CI, 0.12;1.20, p = 0.02) were significantly associated with the development of CCA. For the subpopulation with data on joint involvement in the acute phase, the risk factors significantly associated with CCA were at least one 1 enthesitis (RD 16.7, 95%CI, 2.8; 30.7, p = 0.02) and at least one tenosynovitis (RD 16.8, 95% CI, 1.4-32.2, p = 0.04). CONCLUSIONS:This cohort study conducted in Martinique confirms that CCA is a common complication of acute chikungunya disease. Our analysis emphasized the importance of age and female sex for CCA occurrence, and highlighted the aggravating role of dehydration during the acute phase. Early and adequate hydration were found to reduce the risk chronic chikungunya disorders. TRIAL REGISTRATION:clinicaltrials.gov (NCT01099852).